Effectiveness Of Using E-Filing On Improving Individual Taxpayer Compliance With Mastery Of Accounting Information Systems As A Moderating Variable - Sholih, Muhammad Wildan; Ubaidillah, Muhammad; Umma, I'ana; Prayogo, Imam; Setyaningrum, Pratita Ayu (JRB-Jurnal Riset Bisnis, 2023)
The development of a country depends on how much tax can be collected by the government to finance the running of the government. Taxpayer compliance to pay and report taxes has been widely studied. One of the variables that can increase taxpayer compliance is the use of e-filing to report taxes. Some studies have found that e-filing can increase individual taxpayer compliance, while other studies have the opposite result. This study includes the variable mastery of accounting information systems as a moderating variable that strengthens the effect of e-filing on individual taxpayer compliance. This research was conducted by distributing 100 questionnaires to Individual Taxpayers at the Pekalongan City Tax Office. Research variables were tested using the Partial Least Square method with the SmartPLS 3.0 application. The results show that the e-filing variable has a significant positive effect on individual taxpayer compliance. The results of the second hypothesis indicate that the accounting information system mastery variable does not moderate the effect of e-filing on individual taxpayer compliance. This may be because the tax office has succeeded in educating taxpayers about using e-filing.